Device-independent quantum key distribution using single-photon entanglement - Kamaruddin, Suhaili; Shaari, Jesni Shamsul (IOP Science, 2015)
Quantum key distribution (QKD) with security features based on the notion of nonlocality has provided valuable insights into the possibility of device-independent scenarios. The essential resource for nonlocality in Nature described by quantum physics has been mainly associated with entanglement of two particles or more, although it has been shown that nonlocality of a single particle is indeed possible. Here, we consider a quantum key distribution scheme based on Phys. Rev. A, 68 (2003) 012324 exploiting single-particle nonlocality testing to demonstrate its security. We present our analysis of security against individual attack within a device-independent scenario where Eve is constrained only by the no-signaling principle. We further consider a family of QKD protocols based on binary measurements and discuss the possibility of optimal scenarios.